Identitas Komunikasi Virtual Youtuber di Media Youtube (Studi Kasus Vtuber di Jakarta) - Paskalis Damar Adileksono; Prahastiwi Utari (Universitas Sebelas Maret (UNS), 2024)
Live streaming is a result born from the growth of communication media. One form of live streaming are Virtual youtubers or vtubers who uses animated characters as a representation of themselves.This research was conducted to analyze the communication identity of the vtuber itself. Seeing how identity is formed based on the person, their role, relationships with others and with the community. The research is based on the theory of Communication Identity emphasizing the four frameworks of communication identity formation in the formation of vtuber identity. The research uses qualitative methods with data collection in the form of direct interviews. The subject of data collection is an Indonesian vtuber who does live streaming on YouTube media. Sampling was done by purposive method and obtained 13 respondents. The results found that the identity of a vtuber is made based on a value that they want to bring. This value is realized and played through the character it creates or gives. The identity of the character is bound or similar to the personal identity of the person in it. Identity will be released when dealing with other vtubers, but on the contrary, it will be played as well as possible when interacting within the community.